2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6855117
|View full text |Cite
|
Sign up to set email alerts
|

Compressive hyperspectral imaging using progressive total variation

Abstract: Compressed Sensing (CS) is suitable for remote acquisition of hyperspectral images for earth observation, since it could exploit the strong spatial and spectral correlations, allowing to simplify the architecture of the onboard sensors. Solutions proposed so far tend to decouple spatial and spectral dimensions to reduce the complexity of the reconstruction, not taking into account that onboard sensors progressively acquire spectral rows rather than acquiring spectral channels. For this reason, we propose a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Compared to the existing RPCA model [23], [27], it can be clearly observed that the constraint of the rank of the clean image being no larger than the number of endmembers is added in model (18). The rank of the matrix X, which is an intrinsic feature of an HSI image, is very meaningful in the HSI restoration process.…”
Section: A Low-rank Matrix Factorization-based Hsi Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the existing RPCA model [23], [27], it can be clearly observed that the constraint of the rank of the clean image being no larger than the number of endmembers is added in model (18). The rank of the matrix X, which is an intrinsic feature of an HSI image, is very meaningful in the HSI restoration process.…”
Section: A Low-rank Matrix Factorization-based Hsi Restorationmentioning
confidence: 99%
“…In [17], a spatial spectral TV approach was used for HSI restoration. In [18], Kuiteing et al proposed an iterative TV architecture for HSI reconstruction. Taking the spectral noise differences and the spatial information differences into consideration, Yuan et al [19] proposed an HSI restoration algorithm employing a spectral spatial adaptive TV (SSAHTV) model.…”
Section: Introductionmentioning
confidence: 99%
“…We compared our results to those achieved by the iterative total variation algorithm (ITV) introduced in Ref. 37 In order to test the performance of the algorithm, acquisition and reconstruction of hyperspectral images from the AVIRIS Yellowstone dataset proposed in Ref. 2 were simulated.…”
Section: Resultsmentioning
confidence: 98%
“…A method that relies on separate sensing of spectral rows and that is compatible with onboard systems with a pushbroom configuration was proposed in Ref. 37. Last, hyperspectral imagers based on a single pixel camera architecture were introduced in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition is iterated while changing the pattern of the spatial modulator, thus measuring several elements of the involved integral transform. Information regarding the signal estimation algorithms developed in the framework of the Project have been discussed in [14]. Some preliminary measurements for the experimental assessment of CS performance and the related reconstruction errors are also shown.…”
Section: Introductionmentioning
confidence: 99%